Numerical parameters of island glaciers obtained using digital stereophotogrammetry - Glotov, V. N.; Kovalonok, S. B.; Chizevskiy, V. V. (Ukrainian Antarctic Journal, 2004)
Recent observations of the small ice cap of Galindez Island have shown significant changes since the 1950s. The mean annual temperature in the island region increased by over 2C° during the past 40 years up to about -4°C. Temperature observations show that the mean annual temperature increased from about -5.8°C in the late 1940s to -3.0°C in the mid 1990s. Studies of the Galindez ice cap have been carried out from the commencement of Faraday/Vernadsky operations. The 1961 survey shows a reduced area enclosed by the fifty meters contour and this may reflect recession following the very mild period in the late 1950s. The BAS surveys prior to 1987 show only small variations in the maximum height of the ice cap, which was between 55 and 56 meters high. The most noticeable change of the ice cap occurred in the bay opposite Wordie House. The ice rested on rock is close to mean sea level and so it is affected by marine erosion at high tides. Although the bulk of the ice cap is receding, visual observation shows that the change is not uniform over the entire ice cap. Analyses of digital phototheodolite method using for island glaciers researches in the Vernadsky region are presented in the paper. The present observations show a reduction of about 2-3 per cent of the Galindez ice cap volume in 2002-2004. It is suggested that the ice cap can disappear by the end of the current century.